EU Private International Law in Family and Succession Matters: The Hungarian Judicial Practice - Nagy, Csongor István (Pécs journal of international and European law, 2021)
This article is based on the Hungarian strand of the multiyear CEPIL project (“Cross-Border Litigation in Central-Europe: EU Private International Law before National Courts”) carried out with the generous support of the European Commission Directorate General Justice and Con- sumers. One of the leading considerations behind the CEPIL project was that the value of private international law (PIL) unification can be preserved only if EU private international law (EU PIL) instruments are applied correctly and uniformly, hence, the European endeavors in the field should not and cannot stop at statutory unification but need to embrace the judicial practice and make sure that besides the vertical communication between the CJEU and national courts, there is also a hor- izontal communication between national courts, authorities and the legal community in general. The purpose of this publication is to contribute to this horizontal communication between Member State courts by providing an analytical insight into the Hungarian case-law on EU PIL instruments in family and succession matters.